2014
DOI: 10.1038/nrgastro.2014.200
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk at the mucosal border: importance of the gut microenvironment in IBS

Abstract: The aetiology and pathology of IBS, a functional bowel disorder thought to lack an organic cause, is largely unknown. However, studies suggest that various features, such as altered composition of the gut microbiota, together with increased intestinal permeability, a changed balance in the enteroendocrine system and a dysregulated immune system in the gut, most likely have an important role in IBS. Exactly how these entities act together and give rise to symptoms is still unknown, but an altered gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(152 citation statements)
references
References 216 publications
2
148
0
2
Order By: Relevance
“…There is a blossoming literature on this topic, and excellent reviews conclude that it is clear that the colonic microbiome may play a major role in IBS [79][80][81][82]. A summary of current thinking is presented below [79][80][81][82] 1. In animal studies it has been shown that the colonic microbiome alters visceral pain responses, intestinal permeability and brain function and behaviour.…”
Section: The Gut Microbiome-stomach Duodenum and Colonmentioning
confidence: 99%
“…There is a blossoming literature on this topic, and excellent reviews conclude that it is clear that the colonic microbiome may play a major role in IBS [79][80][81][82]. A summary of current thinking is presented below [79][80][81][82] 1. In animal studies it has been shown that the colonic microbiome alters visceral pain responses, intestinal permeability and brain function and behaviour.…”
Section: The Gut Microbiome-stomach Duodenum and Colonmentioning
confidence: 99%
“…En la fisiopatología del SII participan diversos factores, entre ellos ha sido ampliamente descrita la presencia de alteraciones biológicas que afectan la comunicación neuro-inmune de la mucosa intestinal 14 , proceso que se ve favorecido frente a condiciones genéticas predisponentes 15 . Dentro de los mecanismos biológicos alterados se incluyen: la activación de células inmunes en la mucosa intestinal, tales como linfocitos T, linfocitos B y mastocitos; las alteraciones en la composición y aumento del número de la microbiota intestinal, que llevan al procesamiento anormal de moléculas presentes en la dieta; y la mayor liberación de sustancias bioactivas por células enterocromafines (EC) 11,14,16,17 .…”
Section: Artículo Originalunclassified
“…Dentro de los mecanismos biológicos alterados se incluyen: la activación de células inmunes en la mucosa intestinal, tales como linfocitos T, linfocitos B y mastocitos; las alteraciones en la composición y aumento del número de la microbiota intestinal, que llevan al procesamiento anormal de moléculas presentes en la dieta; y la mayor liberación de sustancias bioactivas por células enterocromafines (EC) 11,14,16,17 . La respuesta inflamatoria intestinal es reforzada por una mayor actividad nerviosa entérica, relacionada al aumento de la sensibilidad visceral e incremento en la estimulación de terminales nerviosos aferentes y a la alteración del eje intestino-cerebro en estos pacientes 18 .…”
Section: Artículo Originalunclassified
“…Increased mucosal permeability is frequently observed in IBS and can be caused by specific pathogens and diet (cow milk allergy or high fat diet), especially in patients with susceptibility genes. 133,134 Activation of mucosal mast cells by short-chain fatty acid (through short-chain free fatty acid receptor 2 [FFA2]) and other stimuli triggers the release of specific proteases and inflammatory cytokines which further increase mucosal permeability. 135 Dysregulated repair/ regenerative signals (Wnt, Notch, and TGF-β) could also contribute to the barrier leakage by their effects on cell-cell-junction, function and number of secretory cells and their indirect effects through immune cells.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%